Exercise, Caloric Restriction, and Systemic Oxidative Stress. (1st March 2006) - Galassetti, Pietro R.; Nemet, Dan; Pescatello, Andria; Rose-Gottron, Christie; Larson, Jennifer; Cooper, Dan M.
Abstract : Background: In humans, the main sources of reactive oxygen species (ROS), the molecules causing oxidative stress, are mitochondrial superoxide ions and neutrophil-derived oxidative radicals. Circulating antioxidants contribute to the protection against oxidative stress. Although the formation of ROS and secretion of antioxidants are independently regulated by exercise and diet, little is known about their combined effect. We hypothesized that relatively brief, intense exercise training may reduce systemic oxidation via an intrinsic mechanism, independent of changes in circulating antioxidants and of neutrophil-derived enzymes (as may be caused by concomitant caloric restriction). Methods: Nineteen volunteers exercised for 7 days, 3 hours/day at 75% of oxygen uptake. Caloric intake was either 110% of caloric expenditure (high calorie, n = 10) or 75% of caloric expenditure (low calorie, n = 9). Blood samples for F2-isoprostanes, catalase, myeloperoxidase (MPO), interleukin-x (IL-x), white blood cells (WBCs), and other metabolic variables were taken at baseline, at the end of training, and 1 week after completion of the study. Results: Serum F2-isoprostanes (μg/mL), markers of lipid peroxidation, were similarly reduced after 7 days of exercise in the high-calorie (from 35 ± 4 to 27 ± 2) and low-calorie (from 35 ± 3 to 24 ± 2) groups. Similar reductions were observed in IL-x concentrations. Conversely, no change was observed in circulating concentrations of the antioxidant catalase. Whereas total WBCs and neutrophil counts were significantly reduced in the low-calorie group only, no difference in neutrophil-derived MPO was measured between groups. Conclusion: A significant reduction in systemic oxidation may occur relatively early during intense exercise training in healthy young men, independent of caloric intake. The potential contribution to these effects of circulating antioxidants and neutrophil-derived oxidative enzymes will require further investigation.